The Performance Achievement of Bureaucratic Reform in Bima Regency: A Perspective of Public Administration - Arman, Arman; Junaidin, Junaidin; Haeril, Haeril (Jurnal Pemerintahan dan Politik Lokal, 2024)
This research aims to analyze the achievements of bureaucratic reform in Bima Regency, Indonesia, with a focus on the aspects of transparency in public administration, the application of merit system in employee management, optimization of public services, and the implementation of bureaucracy simplification policies based on information technology. In this context, the research highlights the importance of these aspects in enhancing accountability, efficiency, and quality of public services. The research methodology used is qualitative descriptive, collecting data through interviews, literature reviews, and data analysis from primary and secondary sources. The results of the research indicate that the implementation of bureaucratic reform in Bima Regency has progressed, especially in terms of transparency in public administration, the application of merit system, and the adoption of information technology. The Unqualified Opinion from the Supreme Audit Agency (BPK) on the Regional Government Financial Report signifies success in maintaining transparency, while the adoption of E-Government applications has improved efficiency and transparency in various government sectors. However, there are still challenges such as deviations in employee selection procedures and complaints regarding the quality of public services, indicating the need for additional steps to ensure the overall success of bureaucratic reform. Despite obstacles in implementation, these positive trends reflect successful efforts in adopting information technology as a tool to enhance administrative efficiency and the quality of public services, reflecting the commitment of local governments to improve governance that is more efficient, transparent, and responsive to the needs of the community.